Bond strength of adhesive systems to human tooth enamel Resistência adesiva de sistemas adesivos ao esmalte dentário humano - Thaís Cachuté Paradella; Marcelo Fava (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The purpose of this study was to evaluate in vitro three adhesive systems: a total etching single-component system (G1 Prime & Bond 2.1), a self-etching primer (G2 Clearfil SE Bond), and a self-etching adhesive (G3 One Up Bond F), through shear bond strength to enamel of human teeth, evaluating the type of fracture through stereomicroscopy, following the ISO guidance on adhesive testing. Thirty sound premolars were bisected mesiodistally and the buccal and lingual surfaces were embedded in acrylic resin, polished up to 600-grit sandpapers, and randomly assigned to three experimental groups (n = 20). Composite resin cylinders were added to the tested surfaces. The specimens were kept in distilled water (37°C/24 h), thermocycled for 500 cycles (5°C-55°C) and submitted to shear testing at a crosshead speed of 0.5 mm/min. The type of fracture was analyzed under stereomicroscopy and the data were submitted to Anova, Tukey and Chi-squared (5%) statistical analyses. The mean adhesive strengths were G1: 18.13 ± 6.49 MPa, (55% of resin cohesive fractures); G2: 17.12 ± 5.80 MPa (90% of adhesive fractures); and G3: 10.47 ± 3.14 MPa (85% of adhesive fractures). In terms of bond strength, there were no significant differences between G1 and G2, and G3 was significantly different from the other groups. G1 presented a different type of fracture from that of G2 and G3. In conclusion, although the total etching and self-etching systems presented similar shear bond strength values, the types of fracture presented by them were different, which can have clinical implications. O objetivo deste estudo foi avaliar in vitro três sistemas adesivos: um monocomponente com condicionamento ácido total (G1 Prime & Bond 2.1), um "primer" autocondicionante (G2 Clearfil SE Bond) e um adesivo autocondicionante (G3 One Up Bond F), através de resistência ao cisalhamento ao esmalte de dentes humanos, avaliando o tipo de fratura por estereomicroscopia, seguindo as normas ISO para testes adesivos. Trinta pré-molares hígidos foram seccionados ao meio em sentido mésio-distal, incluídos em resina acrílica, polidos até lixa d'água de granulação 600 e aleatoriamente divididos em três grupos (n = 20). Cilindros de resina composta foram adicionados às superfícies de teste. Os espécimes foram armazenados em água destilada (37°C/24 h), termociclados por 500 ciclos (5°C-55°C) e submetidos ao teste de cisalhamento com velocidade de 0,5 mm/min, sendo o tipo de fratura analisado sob estereomicroscopia e os dados submetidos à análise estatística Anova, Tukey e Qui-quadrado (5%). As médias de resistência adesiva foram: G1: 18,13 ± 6,49 MPa, (55% de fraturas coesivas em resina); G2: 17,12 ± 5,80 MPa (90% de fraturas adesivas) e G3 10,47 ± 3,14 MPa (85% de fraturas adesivas). Em termos de resistência adesiva, não houve diferenças significantes entre G1 e G2, tendo G3 apresentado diferença significante em relação aos demais grupos. G1 apresentou tipo de fratura diferente de G2 e G3. Em conclusão, apesar de os sistemas adesivos com condicionamento ácido total e "primer" autocondicionante terem apresentado valores de resistência adesiva similares, o tipo de fratura apresentado por eles foi diferente, o que pode ter implicações clínicas.